Hybrid surgery for coexistence of cerebral arteriovenous malformation and primitive trigeminal artery: A case report and literature review - Wang, Lesheng; Li, Jieli; Li, Zhengwei; Chai, Songshan; Chen, Jincao; Xiong, Nanxiang; Yang, Bangkun (Frontiers in Surgery, 2022)
The primitive trigeminal artery (PTA), an abnormal carotid-basilar anastomosis, forms the vascular anomaly connection between the internal carotid artery and vertebrobasilar system. Rarely, PTA can be complicated by several other cerebrovascular disease, including arteriovenous malformations (AVMs), intracranial aneurysms, moyamoya disease, and carotid-cavernous malformations. Herein, we reported a rare case of PTA combined with an AVM in a male patient. The patient was a 28-year-old male with epileptic seizures at the onset of symptoms. Magnetic resonance imaging showed abnormal signal foci and localized softening foci formation with gliosis in the right parietal temporal lobe. Furthermore, using a digital subtraction angiogram (DSA), it was found that an abnormal carotid-basilar anastomosis had developed through a PTA originating from the cavernous portion of the right internal carotid artery (ICA) and a large AVM on the surface of the right carotid artery. The lesion of AVM tightly developed and draining into superior sagittal sinus. A hybrid operating room was used for the surgery. The main feeding arteries of the AVM originating from three major arteries, including the right middle cerebral artery, the right anterior cerebral artery, and the right posterior cerebral artery, were clipped and subsequently, then the AVM was thoroughly removed. The intraoperative DSA showed that the AVM had been resected completely. Postoperative pathological examination of the resected specimen indicated the presence of an AVM. The patient recovered well after surgery and has been symptom-free for more than 3 months. In summary, the pathogenesis of the coexistence of PTA and AVM remains unknown. As highlighted in this case report, hybrid surgery can be used to remove AVMs and can improve the patients’ prognosis. To our best knowledge, this is the first case in the literature of successful AVM treatment using hybrid surgery.